Unconventional monetary policy and the portfolio choice of international mutual funds. (July 2021) - Cenedese, Gino; Elard, Ilaf
Highlights: Large-scale asset purchases (LSAPSs) have significant global spillover effects. Mutual fund managers rebalance portfolios across developed markets following LSAPs. We find little evidence for fund managers contributing to QE-induced flows to EMs. Abstract: This paper analyses how unconventional monetary policy by the major central banks in developed markets affects the geographical portfolio choice of international mutual fund managers. We find that large-scale asset purchases have significant international spillover effects, in contrast to unconventional monetary policy announcement surprises. Specifically, we document that mutual fund managers rebalance their portfolios away from the developed country conducting large-scale asset purchases and towards other developed markets. We find little evidence for fund managers contributing to QE-induced capital flows to emerging markets.